Vector Magnetometry Based on Polarimetric Optically Detected Magnetic Resonance. Issue 11 (27th September 2022) - Reuschel, Philipp; Agio, Mario; Flatae, Assegid M.
Abstract: A robust technique is introduced for vector magnetometry based on polarimetry and optically detected magnetic resonance of ensembles of negatively charged nitrogen‐vacancy (NV – ) centers in diamond without a magnetic bias field. Ensembles provide a far greater signal‐to‐noise ratio than single centers, and their creation requires less effort. Previous methods for vector magnetometry using ensembles of NV – centers relied on a calibrated magnetic bias field or on complex detection techniques to distinguish the crystal axes. Instead, this work uses out‐of‐plane polarized light to selectively excite NV – centers oriented along specific crystal axes. This approach is general for other spin‐1 color centers with C 3 v C_3v symmetry, and it is compatible with standard microscopy methods, such as scanning probe, superresolution, confocal, and wide‐field imaging. Abstract : The optically detected magnetic resonances of negatively charged nitrogen vacancy (NV – ) centers in diamond are combined with polarimetry to determine the magnitude and direction of an unknown magnetic field. A longitudinal laser polarization component enables the unequivocal distinction of the four crystal axes containing NV – centers, allowing high sensitivity and robust vector magnetometry without a magnetic bias field.